Salary and Wage Management in the Early Islamic Era: A Survey of Military Pay Management - Basir, Aminudin; Umar, Azizi; Kaharudin, Iszan Hana; Alias, Jamsari; Yaacob, Mashitoh; Hassan, Wan Zulkifli Wan; Rahman, Mohd Syuhaimi Ab; Mat, Norazila; Saufi, Suraini (Journal of Ecohumanism, 2025)
Human resource management is one of the things that are given serious attention by Islamic teachings. This is because the management of that aspect involves the use of energy and individual minds to achieve the organisation’s objectives. And one aspect of the human resource management that is emphasized by Islam is the payment of salaries or wages to employees. Related to this aspect, there is a misunderstanding from some members of the society or managers of an organization who thinks that employees need to sacrifice more beyond the pay rate, especially when the sacrifice is related to religion. As a result, workers feel burdened to meet and support life when the salaries or wages received are not commensurate with the energy poured into the work. Thus, question related on what is the position of wages or salaries according to Islamic teachings on work arises? How was the practice regarding payment of wages or salaries in the early days before the Islamic Golden Age? Is there a salary and rank increment system practiced in the era of the Islamic Caliphate? With that, this writing will review the position of salary or wages according to Islamic teachings and the implementation of the salary or wages distribution system during the time of the Prophet SAW until the time of the Four “Rightly Guided” Caliphs (Abu Bakar, Umar, Uthman and Ali). This study will also look at the salary and rank increment system implemented after the era of the Four Caliphates. In order to achieve the objectives of the study, qualitative researched methodology was used to obtained and analysed data, especially from written materials. The study found that Islamic teachings emphasised the importance of fair wages or compensation for work and prohibit being unjust towards workers. The study results also show that the salary and wage management system was implemented during the time of the Prophet Muhammad SAW and the era of the “Four Rightly Guided” Caliphs. Furthermore, this study also proves that there is a system of salary and promotion increment that has been practiced in Islamic governance after the era of the Four “Rightly Guided” Caliphs.